Use of audiovisual aids to improve listening comprehension (2020)
This qualitative study seeks to find limitations affecting students’ performance in listening exercises. This study also looks to help students to improve their listening skills through the application of listening strategies. These strategies are applied to listening activities based on audiovisual aids. The research questions which guides are two: First, how can listening comprehension be improved in seventh grade English class at La Enseñanza School in Barranquilla? Second, how can audiovisual aids be implemented as pedagogical resource to improve listening comprehension? The first step is to apply techniques which allows us to analyze student’s performance in English exercises. With the observation process, we can determine the behavior, feelings and knowledge of the students. With the application of a learning styles test we can identify the best way in which each student learns.” Finally, a diagnostic test is applied to determine students English level. The students are studying in a private school where English is thought as a foreign language. Many studies have been oriented to improve listening skills using different tools and strategies. This study seeks to do it using audiovisual aids as the pedagogical tool to improve listening comprehension. Authors such as Mossa (2013) helps us to design the activities in order to know how to apply audiovisual aids and listening strategies previously thought to the students, and Ramirez.J and Alvarez.D (2016) make us aware of the importance of having an adequate classroom with the necessary tools to do listening exercises. All of this information was taking into account at the time to apply our proposal in order to give all the optimal conditions to the students to improve their performance in English listening exercises.